(untitled) (KULT_online, 2011)
The contributors to the edited volume Hochschule als transkultureller Raum? Kultur, Bildung und Differenz in der Universität (Academia As a Transcultural Space? Culture, Education, and Difference in the University), published by Lucyna Darowska, Thomas Lüttenberg, and Claudia Machold, discuss the meaning and significance of the terms culture, transculture, and education within the sphere of higher education. The compiled articles, taken together, are supposed to shed light on the extent to which the concept of transculturality adequately accounts for the actual circumstances in institutions of higher education, in practice, on a descriptive level (p. 8). Also underlying this is the normative question of measures necessary to enable higher education to become a transcultural space. With this essay collection, the editors, coming from political sciences, history, and pedagogics, introduce the concept of transculturality as a suitable objective for higher education in the 21st century that can meet the requirements of the phenomena of migration and internationalization.